Benign prostatic hyperplasia/obstruction ameliorated using a soluble guanylate cyclase activator. Issue 4 (15th February 2022) - Zabbarova, Irina V; Ikeda, Youko; Kozlowski, Mark G; Tyagi, Pradeep; Birder, Lori A; Chakrabarty, Basu; Perera, Subashan KPG; Dhir, Rajiv; Straub, Adam C; Sandner, Peter; Andersson, Karl‐Erik; Drake, Marcus J; et al.
Abstract: Benign prostatic hyperplasia (BPH) is a feature of ageing males. Up to half demonstrate bladder outlet obstruction (BOO) with associated lower urinary tract symptoms (LUTS) including bladder overactivity. Current therapies to reduce obstruction, such as α1‐adrenoceptor antagonists and 5α‐reductase inhibitors, are not effective in all patients. The phosphodiesterase‐5 inhibitor (PDE5I) tadalafil is also approved to treat BPH and LUTS, suggesting a role for nitric oxide (NO ), soluble guanylate cyclase (sGC), and cGMP signalling pathways. However, PDE5I refractoriness can develop for reasons including nitrergic nerve damage and decreased NO production, or inflammation‐related oxidation of the sGC haem group, normally maintained in a reduced state by the cofactor cytochrome‐b5‐reductase 3 (CYB5R3). sGC activators, such as cinaciguat (BAY 58‐2667), have been developed to enhance sGC activity in the absence of NO or when sGC is oxidised. Accordingly, their effects on the prostate and LUT function of aged mice were evaluated. Aged mice (≥24 months) demonstrated a functional BPH/BOO phenotype, compared with adult animals (2–12 months), with low, delayed voiding responses and elevated intravesical pressures as measured by telemetric cystometry. This was consistent with outflow tract histological and molecular data that showed urethral constriction, increased prostate weight, greater collagen deposition, and cellular hyperplasia. All changes in aged animals were attenuated by daily oral treatment with cinaciguat for 2 weeks, without effect on serum testosterone levels. Cinaciguat had only transient (1 h) cardiovascular effects with oral gavage, suggesting a positive safety profile. The benefit of cinaciguat was suggested by its reversal of an overactive cystometric profile in CYB5R3 smooth muscle knockout mice that mirrors a profile of oxidative dysfunction where PDE5I may not be effective. Thus, the aged male mouse is a suitable model for BPH‐induced BOO and cinaciguat has a demonstrated ability to reduce prostate‐induced obstruction and consequent effects on bladder function. © 2021 The Pathological Society of Great Britain and Ireland.